"True" versus "apparent" stage I epithelial ovarian cancer: value of frozen section analysis. (1st January 2006) - Naik, R.; Cross, P.; Lopes, A.; Godfrey, K.; Hatem, M. H.
Abstract : The aim of this prospective study was to determine the clinical benefits of introducing peroperative frozen section analysis into the surgical management policy of women referred with an adnexal mass suspicious of ovarian cancer. All women surgically managed at the Northern Gynaecological Oncology Centre, Gateshead, UK, between July 1, 2002, and June 30, 2003, where frozen section analysis had been utilized were included for analysis. Correlation was determined between cases surgically staged following the frozen section result and the clinical need for staging based on the pathologic diagnosis from the paraffin section. During the 12-month period, 130 women underwent frozen section analysis. Paraffin section diagnoses included 74 benign tumors, 11 borderline tumors, 34 primary epithelial cancers, 5 nonepithelial cancers, and 6 metastatic tumors. All primary epithelial ovarian cancers were correctly identified as requiring a staging procedure based on the frozen section result. Four of seventy-four cases reported as benign on frozen section analysis were underdiagnosed; two were later diagnosed on paraffin section as borderline tumors and a further two as malignant (one low-grade adenosarcoma and one primary peritoneal cancer). Of the 130 cases, 55 (42.3%) underwent a staging procedure based on the frozen section result. The value of frozen section analysis in determining the need for the performance of a staging procedure had the following statistical test results: sensitivity = 92%, specificity = 88%, positive predictive value = 82%, and negative predictive value = 95%. Excluding the borderline tumors, metastatic tumors, and primary peritoneal tumor where staging did not impact subsequent clinical management, the statistical test results for frozen section analysis in determining the need for a staging procedure were sensitivity = 97%, specificity = 95%, positive predictive value = 90%, and negative predictive value = 99%. The clinical benefits of introducing frozen section analysis in the surgical staging policy of women with an adnexal mass suspicious of ovarian malignancy included avoidance of a surgical staging procedure in 95% of cases identified on paraffin section analysis to be benign. This benefit was without compromising the avoidance of chemotherapy in true stage I epithelial ovarian cancer cases. Additional benefits included the confirmation of malignancy where extraovarian lesions were suggestive but not indicative of malignant disease, and the intraoperative identification of metastatic disease of nonovarian origin.